Activation of carcinogens by peroxidase. Horseradish peroxidase-mediated formation of benzenediazonium ion from a non-aminoazo dye, 1-phenylazo-2-hydroxynaphthalene (Sudan I) and its binding to DNA - Stiborová, M; Asfaw, B; Anzenbacher, P (FEBS letters, 1988)
Horseradish peroxidase in the presence of hydrogen peroxide (HRP/H2O2) oxidizes a carcinogenic non-aminoazo dye, 1-phenylazo-2-hydroxynaphthalene (Sudan I) to the ultimate carcinogen, which binds to calf thymus DNA. The principal product of Sudan I oxidation by the HRP/H2O2 system is the benzenediazonium ion. Minor products are hydroxy derivatives of Sudan I, in which the aromatic rings are hydroxylated. The principal oxidative product (the benzenediazonium ion) is responsible for the carcinogenicity of Sudan I, because this ion, formed from this azo dye, binds to DNA.
Keywords: Peroxidases; křenová peroxidasa; Oxidation-Reduction; peroxid vodíku; Diazonium Compounds; Edaravone; Animals; spektrofotometrie; Hydrogen Peroxide; skot; Naphthols; peroxidasy; naftoly; Spectrophotometry; fenazon; edaravon; oxidace-redukce; Carcinogens; karcinogeny; DNA; zvířata; diazoniové sloučeniny; Cattle; Horseradish Peroxidase; Antipyrine